2009
DOI: 10.1158/1078-0432.ccr-08-1818
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-451 Regulates Macrophage Migration Inhibitory Factor Production and Proliferation of Gastrointestinal Cancer Cells

Abstract: Purpose: microRNAs (miRNA) are small RNAs that function as post-transcriptional regulators of gene expression. Recent evidence has shown that some miRNAs can act as oncogenes or tumor suppressors. This study was conducted to evaluate the potential association of miRNA expression with clinical outcome in patients with gastric cancer. Experimental Design: Expression of 250 human mature miRNAs was measured by real-time PCR on paraffin-embedded tumor samples of 21 patients with gastric cancer stage III uniformly t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
246
4

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(260 citation statements)
references
References 44 publications
10
246
4
Order By: Relevance
“…Of note, the expression of miR-451 is downregulated in patients who did not respond to irinotecan-based first-line therapy compared with responding patients. A same study showed that miR-451 combined with imatinib mesylate had a cooperative effect on growth inhibition of glioblastoma stem cells (16). Similarly, higher expression of miR-451 and miR-15b in pretreatment osteosarcoma samples correlated with subsequent positive response to neoadjuvant chemotherapy (58).…”
Section: Mir-451 In Cancer Therapymentioning
confidence: 95%
See 2 more Smart Citations
“…Of note, the expression of miR-451 is downregulated in patients who did not respond to irinotecan-based first-line therapy compared with responding patients. A same study showed that miR-451 combined with imatinib mesylate had a cooperative effect on growth inhibition of glioblastoma stem cells (16). Similarly, higher expression of miR-451 and miR-15b in pretreatment osteosarcoma samples correlated with subsequent positive response to neoadjuvant chemotherapy (58).…”
Section: Mir-451 In Cancer Therapymentioning
confidence: 95%
“…miR-29b, miR-29c, miR-19b, miR-31, miR-148a, and miR-451 were highly expressed in gastric tissue and could be considered as a part of the miRNA expression pattern of healthy gastric tissue (47). Likewise, another study detected miR-451 expression in epithelial cells by in situ hybridization and found that miR-451 expression was decreased in gastric and colorectal cancer tissues compared with nontumor tissues (16). We previously also observed that miR-451 was significantly downregulated by 170.9-fold comparing non-small cell lung carcinoma (NSCLC) tissues with corresponding noncancerous tissues (14,15).…”
Section: Mir-451 In Cancer Diagnosismentioning
confidence: 96%
See 1 more Smart Citation
“…Tsuchiya et al (2009) showed that miR-338-3p and miR-451 contributed to the formation of epithelial basolateral polarity by facilitating translocalization of b1-integrin to the basolateral membrane in an epithelial differentiation model. Moreover, miR-451 can also regulate cancer proliferation and metastasis through targeting macrophage migration inhibitory factor (Bandres et al, 2009). Another tumor suppressor miRNA, miR-122, negatively impacts hepatocellular carcinoma intrahepatic metastasis by suppressing angiogenesis, and exerts its action through regulation of the disintegrin and metalloprotease 17 (ADAM17) .…”
Section: Microrna and Metastasis H Zhang Et Almentioning
confidence: 99%
“…The upregulation level of miR-31 was related to the pathological stage of CRC. CRC expression was significantly higher at stage IV than at stage II, indicating that miR-3l could induce tumors and render them with more invasive phenotype, and that miR-31 showed certain clinical effect in staging of CRC (Bandres et al, 2009) used qRT-PCR to examine the expressions of 250 types of miRNAs in the tissues of 21 gastric cancer patients, and the clinical pathological analysis showed that miR-451 was associated with the poor prognosis of gastric cancer patients. In-situ hybridization showed that the expressions of miR-451 decreased in epithelia of gastric cancer and colon cancer patients.…”
Section: Introductionmentioning
confidence: 99%